Select indicators and prioritize solutions for desertification and drought in Binh Thuan, Vietnam. Issue 2 (2nd April 2016) - Hai, Le Trinh; Gobin, Anne; Hens, Luc
ABSTRACT: The link between climate change and desertification is an important global problem for the United Nations Framework Convention on Climate Change (UNFCCC) and the United Nations Convention to Combat Desertification (UNCCD). The coastal provinces in Southern Centre Vietnam are strongly influenced by desertification, which is further exacerbated by climate change. The Delphi method was used to select sustainability indicators and then a method of an analytical hierarchy process was applied to prioritize sustainable solutions in Binh Thuan experts to elicit the causes and effects of desertification. According to the panel of 23 experts, 27 cause (e.g. rainfall and sunshine duration) and 22 effect (e.g. rice and agriculture) indicators were of particular importance to desertification and drought in the province. The highest priorities for cause are given to emigration, followed by income from industry and water supply for household use. The highest priorities for effect in the area are given to socioeconomic criteria, and in particular to the sub-criteria resettlement due to development projects, building hydropower reservoirs, and implementing irrigation schemes. The system of indicators provides useful information for the future studies. This study provides a means to uncover the most important criteria perceived as major contributors to desertification and as such enables policy-makers to prioritize solutions for Binh Thuan (Vietnam) by 2015 and a vision in 2020.